2018
DOI: 10.1103/physreve.98.063002
|View full text |Cite
|
Sign up to set email alerts
|

Supershear bursts in the propagation of a tensile crack in linear elastic material

Abstract: Since the early years of the linear elastic theory of fracture [linear elastic fracture mechanics (LEFM)], scientists have sought to understand and predict how fast cracks grow in a material or slip fronts propagate along faults. While shear cracks can travel faster than the shear wave speed, the Rayleigh wave speed is the limiting speed theoretically predicted for tensile failure. This work uncovers the existence of supershear episodes in the tensile (mode I) rupture of linearly elastic materials beyond the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The paper has found novel local solutions to mode I and mode II fracture in isotropic linear elasticity that describe supersonic and intersonic crack propagation showing remarkable similarities to experimental and computational models previously reported in the literature (Gao et al 2001;Rosakis 2002;Abraham et al 2002;Guo et al 2003;Buehler et al 2003;Hao et al 2004;Petersan et al 2004;Willmott and Field 2006;Radi and Loret 2008;Bizzarri et al 2010;Schubnel et al 2011;Barras et al 2018;Yue et al 2019;Mai et al 2020). Despite these results, no theoretical predictions describing Mach cone solutions had been reported in the literature before.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The paper has found novel local solutions to mode I and mode II fracture in isotropic linear elasticity that describe supersonic and intersonic crack propagation showing remarkable similarities to experimental and computational models previously reported in the literature (Gao et al 2001;Rosakis 2002;Abraham et al 2002;Guo et al 2003;Buehler et al 2003;Hao et al 2004;Petersan et al 2004;Willmott and Field 2006;Radi and Loret 2008;Bizzarri et al 2010;Schubnel et al 2011;Barras et al 2018;Yue et al 2019;Mai et al 2020). Despite these results, no theoretical predictions describing Mach cone solutions had been reported in the literature before.…”
Section: Discussionsupporting
confidence: 73%
“…However, recent results both experimental and computational have shown crack propagation at significantly higher speeds both in the intersonic range and even beyond the speed of sound (Rosakis et al 1999;Needleman 1999;Abraham and Gao 2000;Huang and Gao 2001;Gao et al 2001;Rosakis 2002;Abraham et al 2002;Guo et al 2003;Buehler et al 2003;Hao et al 2004). Moreover, some of the published results exhibit features akin to shock waves of supersonic flow where solution discontinuities are seen to emerge from the crack tip as it travels along the material (Petersan et al 2004;Willmott and Field 2006;Radi and Loret 2008;Bizzarri et al 2010;Schubnel et al 2011;Barras et al 2018;Yue et al 2019;Mai et al 2020). No analytical models have been reported that predict such behaviour in linear elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless there are applications where an interfacial crack study is required along a predefined path, for example, in geosciences when a weak interface is to be studied, [48][49][50][51] when rough cracks may, under mixed-mode loading, produce interlocking stresses increasing the shear strength [52][53][54][55][56][57][58][59][60] or in the study of adhesive bonds in laminar structures.…”
Section: Isotropic Body Weak Interfacementioning
confidence: 99%
“…Numerical modeling of frictional sliding has been under increased scrutiny. The Boundary Integral Method (BIM) [27] has been widely used to simulate rupture propagation on frictional interfaces [28,29,12,13]. Although computationally efficient, BIM is mostly limited to planar interfaces in infinite domains.…”
Section: Introductionmentioning
confidence: 99%